2018
DOI: 10.1021/acsnano.8b04050
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Deformations at the Interface of a Mixed-Dimensional van der Waals Heterostructure

Abstract: Molecular self-assembly due to chemical interactions is the basis of bottom-up nanofabrication, whereas weaker intermolecular forces dominate on the scale of macromolecules. Recent advances in synthesis and characterization have brought increasing attention to two- and mixed-dimensional heterostructures, and it has been recognized that van der Waals (vdW) forces within the structure may have a significant impact on their morphology. Here, we suspend single-walled carbon nanotubes (SWCNTs) on graphene to create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…39 This is even more evident in the atomically resolved closeups shown in Figure 4b and Supplementary Figure S1. Now, assuming that a minor alignment of interfaces is also possible at room temperature during the nanotube deposition 39 and noting that the mea- to the inter-tube contact morphology. 45 Their observation was that so called tube-tube Yjunctions, which our elongated graphene/SWCNT interfaces superficially resemble, were generally more conductive than simple point contacts (X-junctions).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…39 This is even more evident in the atomically resolved closeups shown in Figure 4b and Supplementary Figure S1. Now, assuming that a minor alignment of interfaces is also possible at room temperature during the nanotube deposition 39 and noting that the mea- to the inter-tube contact morphology. 45 Their observation was that so called tube-tube Yjunctions, which our elongated graphene/SWCNT interfaces superficially resemble, were generally more conductive than simple point contacts (X-junctions).…”
mentioning
confidence: 80%
“…Looking at the optical absorption spectra (OAS, Figure 3c Interfacing of SWCNTs and graphene can be studied using atomically resolved scanning transmission electron microscopy (STEM, see Methods). 39 We first exposed the sample surfaces for observations by applying laser cleaning in the microscope column, 40 using a 10 ms pulse length with a total energy of 60 mJ. Our earlier observations revealed that when the thermodynamic constraints allow, thermophoretically deposited nanotubes form hundreds of nanometers long preferentially stacked interfaces with graphene.…”
mentioning
confidence: 99%
“…The torsion flag for molecular orbitals was disabled, which best matched with our earlier experimental results. [16] The model system consisted of a 30.50 nm × 16.50 nm graphene sheet brought to a distance of 0.8 nm from a pair of crossed (10,10) nanotubes. The cell size was a 96.6 nm triclinic cell where, to achieve periodic boundary conditions, four nanotubes were crossed by 60° angles.…”
Section: Methodsmentioning
confidence: 99%
“…Based on measurement in reciprocal space, the chiral angle of the tube is ≈21° and thus, the chiral indices are (9,5). The graphene envelope is randomly oriented around the tube wall, as can be seen from the rotational mismatch of SWCNT layer lines (L x ) and graphene reflections, [16] although the top and the bottom layers are mutually aligned. The random stacking-order is in agreement with the measured 3.9 Å vdW spacing (Figure 1f inset), which is about 15% larger than expected for AB-stacked graphene.…”
Section: Morphology and Growth Mechanismmentioning
confidence: 99%
“…Scanning transmission electron microscopy (STEM) imaging and electron energy loss spectroscopy allow us to directly identify the heteroatoms, their bonding environment and configuration in the materials. A graphene-SWCNTs heterostructure was used as a target material, with nanotubes synthesized using a floating catalyst method and dry-deposited on graphene [6]. The samples were introduced into the vacuum system connected to the Nion UltraSTEM 100 microscope in Vienna [7], and characterized at atomic resolution.…”
mentioning
confidence: 99%